Modelowa charakterystyka centrów strategiczno-decyzyjnych w spółce o charakterze publicznym - Czapiewski, Mirosław; Kreft, Zbigniew (The model profile of the strategic and decision making centres in a public company, 2005)
The article includes the presentation of the problem concerning the planning of organizational solutions in a public company. Authors, on the basis of their own experience gained during the economic practice, present issues on the modeling of the organizational structure in a capital company of the public profile. As the example of the planning solutions prepared for the Port of Gdynia Managing Board, the problem concerning the development of variants of location of the decision making centers in a modem holding organization is discussed in the article as well as the determinants of the modeling process and planned solutions.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1092, s. 413-421